Small intestinal obstruction due to the metastasis of intrahepatic cholangiocarcinoma: A case report. Issue 12 (March 2018) - Akiyama, Shintaro; Nagahori, Masakazu; Oooka, Shinya; Negi, Mariko; Ito, Takashi; Takenaka, Kento; Ohtsuka, Kazuo; Watanabe, Mamoru
Abstract: Rationale: The small intestine (SI) does not commonly harbor cancer but is occasionally involved by metastatic cancer from other organs. To manage SI cancer appropriately, surveillance for primary origin outside the SI is essential. Patient concerns: This study presents a 54-year-old Thai man diagnosed with SI obstruction which required laparoscopy- assisted partial ileal resection. Diagnoses: On the basis of the expression pattern of cytokeratins (CKs) and mucins (MUCs) in the resected SI adenocarcinoma, we suspected this was metastasized from the pancreatobiliary tract. Imaging studies revealed a hepatic segmental atrophy with an occlusion of the posterior segmental blanch of the portal vein without any contrast-enhanced lesions in the liver. Pathology of the liver biopsy revealed intrahepatic cholangiocarcinoma (ICC) with the same expression pattern of CKs and MUCs as the SI adenocarcinoma. Interventions: Systemic chemotherapy (gemcitabine and cisplatin) was initiated. Outcomes: Despite of the chemotherapy for 20 months, he died of ICC. Lessons: This is the first case of SI obstruction caused by the metastasis of ICC. We demonstrate that immunohistochemical staining of CKs and MUCs discriminate between primary and metastatic SI cancer and predict its primary origin outside the SI. This case also suggests that a hepatic segmental atrophy with portal vein occlusion would be an atypical but important finding to diagnose ICC.